Not My Choice: Feeling as a ‘Productive Paradox’ in Lola Arias’s Doble de riesgo - Bulman, Gail A. (Latin American Theatre Review, 2018)
Framed within Buenos Aires’s Parque de la Memoria, Lola Arias’s 2016 multi-media installation, Doble de riesgo, thrust affect to center stage and highlighted choice as pivotal, emotionally driven, and necessary for individual and collective momentum. The images in Arias’s exhibit thus went beyond inspiring catharsis or compassion; they questioned the role of emotions in creating communities and matters of individual and national security. Using Ben Anderson’s concept of a “productive paradox,” this article shows how Arias seized on the diverse but potent affective aftermath of multiple political and historical events in Argentina, moving her viewers from contemplating individual emotions to participating in collective, affective bonding. This article also pays special attention to the many doubles in Doble de riesgo, examining how Arias expanded and destabilized the notion of the double by transforming its visual elements into trompe-l’oeil—thus highlighting the instability, power, and perpetual shifting of her subjects’ emotions—as well as examining the ways in which the exhibit’s interactive elements made visitors into simultaneous actors and emancipated spectators.